Efeito prebiótico de subprodutos do processamento de frutas tropicais em sistemas de fermentação in vitro - Menezes, Francisca Nayara Dantas Duarte (2020)
The search for foods with prebiotic properties has been the subject of several studies due to their beneficial effects on consumer health. Fruits, due to their high nutrient content, especially the fiber content and the presence of phenolic compounds, are examples of foods with prebiotic potential. This study aimed to evaluate the prebiotic potential of by-products from processing of acerola (Malpighia glabra L.), cashew (Anacardium occidentale L.) and guava (Psidium guajava L.) in in vitro fermentation systems. Initially, the ability of acerola (AB) and guava (GB) by-products, submitted or not to a simulated gastrointestinal digestion, to stimulate the growth and metabolic activity of probiotic strains (Lactobacillus acidophilus LA-05, Lactobacillus casei L-26 and Bifidobacterium animalis subsp. lactis BB-12) was assessed. Digested and undigested AB and GB (20 g/L) stimulated the growth of the probiotic strains, as well as reduced the pH values and increased the production of organic acids and consumption of sugars in culture medium over 48 h. Digested AB and GB (20%, w/v) caused beneficial changes in relative abundance of Bifidobacterium spp., Lactobacillus-Enterococcus, Eubacterium retall-Clostridium coccoides and Bacteroides-Prevotella populations, as well as decreased the pH and increased the production of short chain fatty acids (acetic, butyric and propionic) during 24 h of in vitro colonic fermentation. Sencondly, the impact of the by-product from processing of digested cashew apple (CJ) (20%, w/v) on the relative abundance of bacterial groups present in in vitro colonic fermentation systems was evaluated. Digested CJ increased the relative abundance of Bifidobacterium and Lactobacillus-Enterococcus after 24 h of colonic fermentation, besides to decrease the relative abundance of Bacteroides-Prevotella, Eubacterium retall- C. cocoides and C. hystoliticum. Digested CJ increased the counts of lactic acid bacteria and decreased the counts of Enterobacteriaceae after 24 h of colonic fermentation, in addition to decrease the pH values and increase the production of short chain fatty acids. These results indicate that by-products from tropical fruit processing can be considered candidates for use as prebiotic ingredients because of their capability of stimulating the growth and metabolic activity of beneficial microorganisms found as part of the intestinal microbiota.